Gastric Sclerosing Epithelioid Fibrosarcoma Harboring a Rare FUS-CREM Fusion. (August 2021) - Memon, Raima A.; Granada, Carlos N. Prieto; Patel, Chirag; Manne, Upender; Heslin, Martin J.; Gbolahan, Olumide B; Harada, Shuko; Diffalha, Sameer Al
Sclerosing epithelioid fibrosarcoma (SEF) is a rare, aggressive soft-tissue tumor, commonly occurring in upper and lower extremities, the limb girdle, and the head and neck, which shows morphologic and molecular overlap with low-grade fibromyxoid sarcoma. For SEF in soft tissues, 100 case reports have been published. To our knowledge, the present case is the first to be reported in English literature for a primary SEF of the stomach with a rare FUS-CREM fusion. We report a case of gastric SEF in a 35-year-old female who presented with nonspecific symptoms, including night sweat, cough, and iron deficiency anemia for the past few months. Further workup showed, on computed tomography, a large, heterogeneously enhancing and centrally necrotic left upper quadrant mass, which measured approximately 8.4 cm. A laparoscopic partial gastrectomy with distal pancreatectomy and splenectomy was performed. Histological examination and immunohistochemical staining suggested the diagnosis of primary gastric SEF, which was later confirmed by sarcoma fusion panel showing FUS-CREM fusion. In this article, we report this first case of SEF in the stomach with a rare FUS-CREM fusion, which has been previously reported only once in SEFs of soft tissue.